Inhibin/activin-betaC and -betaE subunits in the Ishikawa human endometrial adenocarcinoma cell line - Kimmich, Tanja; Brüning, Ansgar; Käufl, Stephanie D.; Makovitzky, József; Kuhn, Christina; Jeschke, Udo; Friese, Klaus; Mylonas, Ioannis (Archives of gynecology and obstetrics, 2010)
Inhibins and activins are important regulators of the female reproductive system. Recently, two novel inhibin subunits, named betaC and betaE, have been identified and shown to be expressed in several human tissues. However, only limited data on the expression of these novel inhibin subunits in normal human endometrial tissue and endometrial adenocarcinoma cell lines exist.
Online veröffentlicht am 11. Dezember 2009
Gesehen am 09.03.2023